A Modern Wizard - Ottolengui, Rodrigues, 1861-1937 (Salt Lake City, UT : Project Gutenberg, 2010)
"A Modern Wizard" by Rodrigues Ottolengui is a novel written in the late 19th century. The book unfolds in a period marked by intrigue, suspense, and legal drama, following the story of Dr. Emanuel Medjora, a physician suspected of murder. The narrative begins with young lawyers Mortimer Dudley and Robert Bliss who find themselves entangled in a sensational case involving the mysterious death of Mabel Sloane, a young musician who appears to have been poisoned. The opening of the novel introduces the legal atmosphere of 1873, depicting Dudley and Bliss$1 (Bs aspirations for a high-profile criminal case, which materializes when Dr. Medjora unexpectedly seeks their legal counsel. As the story unfolds, the reader is drawn into a complex web of evidence, including Dr. Medjora's sudden disappearance and the complications surrounding the autopsy results. At the same time, young Jack Barnes, an aspiring detective, becomes embroiled in the mystery as he shadows the enigmatic doctor, leading to dramatic confrontations and revelations. This blend of legal suspense and psychological drama sets the stage for a gripping story of ambition, guilt, and the quest for truth. (This is an automatically generated summary.)s
Release date is 2010-06-27
Produced by Suzanne Shell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Detective and mystery stories, American; Hypnotism -- Fiction